Hasil Reses DPRD dalam Pembuatan Kebijakan di Kota Gunungsitoli - GUSKHAIRINA CHANIAGO (Politeia: Jurnal Ilmu Politik, 2016)
The recess is one of the programs in the legislature. Especially for members of the legislature. This program is an activity outside the office which aims to visiting constituents in their electoral area. A visit to the constituency to accumulate people's aspirations. It is also to monitor developments in the region of their constituents.This study describes how to use the results of the recess of legislators into policymaking in Government Gunungsitoli. The findings of this study, there are three channels that this recess can be accommodated in the policy-making. First, the aspirations of the people who have been accommodated through recess activities are reported in the plenary session (sidang paripurna) of Parliament (DPRD); Second, the aspiration that is obtained when the recess, has been channeled through Musrenbang at government Gunung Sitoli. Third, the results of recess incorporated into public policy budget.This study conducted by an institutional approach and the method used is descriptive method.Keywords: Recession, Parliament, Policy, Local Goverment.